2010
DOI: 10.1186/1471-2407-10-572
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal prostate brachytherapy, using I-125 seed with or without adjuvant androgen deprivation, in patients with intermediate-risk prostate cancer: study protocol for a phase III, multicenter, randomized, controlled trial

Abstract: BackgroundThe optimal protocol for 125I-transperineal prostatic brachytherapy (TPPB) in intermediate-risk prostate cancer (PCa) patients remains controversial. Data on the efficacy of combining androgen-deprivation therapy (ADT) with 125I-TPPB in this group remain limited and consequently the guidelines of the American Brachytherapy Society (ABS) provide no firm recommendations.Methods/DesignSeed and Hormone for Intermediate-risk Prostate Cancer (SHIP) 0804 is a phase III, multicenter, randomized, controlled s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 20 publications
0
49
0
Order By: Relevance
“…The results on univariate and multivariate analyses for intermediate-risk disease identify neoadjuvant CAB as one of the significant favorable factors (table 3), suggesting the potential benefit of neoadjuvant CAB for 6≤ months in intermediate-risk prostate cancer. A prospective, randomized, clinical trial in patients with intermediate-risk prostate cancer comparing NHT plus BT to NHT plus BT plus adjuvant hormone therapy is ongoing to clarify any additional effect of adjuvant hormone therapy [20]. In patients with high-risk localized prostate cancer, a prospective, multicenter, randomized controlled trial for tri-modality therapy with I-125 BT, EBRT and short- or long-term hormone therapy is also ongoing [21].…”
Section: Discussionmentioning
confidence: 99%
“…The results on univariate and multivariate analyses for intermediate-risk disease identify neoadjuvant CAB as one of the significant favorable factors (table 3), suggesting the potential benefit of neoadjuvant CAB for 6≤ months in intermediate-risk prostate cancer. A prospective, randomized, clinical trial in patients with intermediate-risk prostate cancer comparing NHT plus BT to NHT plus BT plus adjuvant hormone therapy is ongoing to clarify any additional effect of adjuvant hormone therapy [20]. In patients with high-risk localized prostate cancer, a prospective, multicenter, randomized controlled trial for tri-modality therapy with I-125 BT, EBRT and short- or long-term hormone therapy is also ongoing [21].…”
Section: Discussionmentioning
confidence: 99%
“…As we introduced in the previous study (6), seed and hormone for intermediate-risk prostate cancer, which is a Phase 3 multicenter trial, is under investigation in Japan. In this trial, 420 patients with intermediate risk were randomized into two groups in which patients either do or do not receive 9 months' adjuvant therapy after PB (24). There are no reports of a prospective study in Japan evaluating the efficacy of ADT with PB for an IRG.…”
Section: Discussionmentioning
confidence: 98%
“…However, this review identified ten ongoing studies which might be able to fill gaps in the current evidence base, thereby demonstrating that RCTs are actively being conducted in this area but it should be noted that this list might not be complete [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. The ProtecT trial will help in this regard and should inform which of radiotherapy, radical prostatectomy and active surveillance should be used in daily clinical practice [40].…”
Section: Implications and Recommendations For Further Researchmentioning
confidence: 96%